Situación actual de los paraísos fiscales (2019)
The purpose of this research is to identify the characteristics of the most important tax havens in the world, the power that the existence of these has in front of the social, political, health and education spheres that together influence the development of the economy world; in addition to the influence that the existence of these tax havens has on the development of the world economy.